Biomechanical and metabolic responses to seat-tube angle variation during cycling in tri-athletes - Bisi, M. C.; Ceccarelli, M.; Riva, F.; Stagni, R. (Journal of Electromyography and Kinesiology, 2012)
One of the most physically demanding parts of triathlon is the transition from cycling to running. Many tri-athletes believe that increasing seat-tube angle (STA) can bring advantages in the following running part. The aim of this study was to evaluate the effects of inverting the support of the seat, for increasing STA, on the metabolic response and on the muscle activation pattern, maintaining a controlled kinematic. Moreover, a muscle-skeletal model was applied to evaluate the hypothesis that increasing STA changes force-producing capabilities of muscles crossing the hip. Ten tri-athletes cycled at two different power levels and with two different STA`s. Gas exchange data, kinematics and surface electromyography (sEMG) were acquired during the tests. sEMG was measured from eight muscles of the right side of the body. A model of muscle mechanics and energy expenditure was applied to estimate variations of force production capabilities and muscle energy consumption between the two STA configurations.